2009
DOI: 10.4049/jimmunol.0900936
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Inhibition and Alloantigen-Specific Regulatory T Cells Synergize To Promote Long-Term Graft Survival in Immunocompetent Recipients

Abstract: Minimization of immunosuppression and donor-specific tolerance to MHC-mismatched organ grafts are important clinical goals. The therapeutic potential of regulatory T cells (Tregs) has been demonstrated, but conditions for optimizing their in vivo function posttransplant in nonlymphocyte-depleted hosts remain undefined. In this study, we address mechanisms through which inhibition of the mammalian target of rapamycin (Rapa) synergizes with alloantigen-specific Treg (AAsTreg) to permit long-term, donor-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 79 publications
2
96
0
Order By: Relevance
“…Similar results were obtained in a murine model of heart transplant in which the adoptive transfer of a small number of alloantigen-specific Treg in the presence of a low dose of RAPA induced long-term survival of cardiac allografts. 50 The beneficial effect of RAPA on Tregs was also observed in a humanized-mouse model where segments of human arterial were transplanted into immunodeficient mice reconstituted with allogeneic human peripheral blood cells. In this model, the authors showed that the presence of RAPA enhanced the ability of sub-therapeutic numbers of human Tregs to prevent transplant rejection.…”
mentioning
confidence: 87%
“…Similar results were obtained in a murine model of heart transplant in which the adoptive transfer of a small number of alloantigen-specific Treg in the presence of a low dose of RAPA induced long-term survival of cardiac allografts. 50 The beneficial effect of RAPA on Tregs was also observed in a humanized-mouse model where segments of human arterial were transplanted into immunodeficient mice reconstituted with allogeneic human peripheral blood cells. In this model, the authors showed that the presence of RAPA enhanced the ability of sub-therapeutic numbers of human Tregs to prevent transplant rejection.…”
mentioning
confidence: 87%
“…Nevertheless, it is becoming evident that, according to the differentiation protocol used, tolerogenic DCs acquired different immune modulatory properties by up-regulating a variety of inhibitory molecules [74, 75•] and the ability to promote the induction of a specific subset of Tregs [7,11]. Despite the number of pre-clinical studies demonstrating feasibility and efficacy of tolerogenic DC immunotherapy [76][77][78][79][80][81], and the efforts dedicated to developing methods to generate clinical-grade tolerogenic DCs [75•, 82], only a limited number of clinical trials have been performed or planned [2,12,82].…”
Section: Dcs As Tolerogenic Cell Productmentioning
confidence: 99%
“…Ex vivo-generated tDCs are considered to have strong potential for use in cellular therapy for these conditions. In fact, injection of ex vivo-generated tDCs has been shown to be beneficial in animal models of graft rejection (8)(9)(10) and autoimmune diseases, including collagen-induced arthritis (11,12), diabetes (13)(14)(15)(16), and experimental autoimmune encephalomyelitis (17). Human tDCs can be cultured in vitro from DC precursors using different compounds (7,18).…”
Section: Endritic Cells (Dcs) Are a Heterogeneous Population Ofmentioning
confidence: 99%